THE RELATION BETWEEN KNOWLEDGE AND ATTITUDE TOWARD BEHAVIOR OF ANTIBIOTIC USAGE ON SOCIETY IN TALANG JAWA HEALTH CENTER OF SOUTH LAMPUNG AUGUST PERIOD 2019 - Lilik Koernia Wahidah (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
In developing countries, many antibiotics are used without a doctor's prescription, causing someone to use antibiotics incorrectly. Lack of knowledge about antibiotics is a major factor that triggers an increase in the rate of bacterial resistance to antibiotics. Knowledge and attitude become one of the social cognitive factors that influence antibiotic use behavior.This study aims to determine the relationship of knowladge and attitudes toward of antibiotic usage behavior in community of Talang jawa public health centre. The research is an observasional analytic research using cross sectional study design. sampling using non-probability sampling methode with type purposive sampling and instruments in the form of questionnaires. The data analysis was based univariate and bivariate analysis eqipped with chi square. The study was conducted on 100 community respondents in the Talang Jawa Health Center. The results showed respondents with good knowledge (25%), enough (27%) and less (48%). Respondents with positive attitudes (64%) and negative attitudes (35%). Respondents with positive behavior (43%) and negative behavior (57%). Chi square test result showed that there was a significant relationship between knowladge and antibiotic use behavior (p= 0,000) and there was a significant relationship between attitude and antibiotic use behavior (p= 0,000). This study has a meaningful relationship between and attitudes with antibiotic use behavior in Talang Jawa Health Center. Keywords: Antibiotics,Knowledge, Attitudes, Behavior